Exploring the connection between canker lesions and inflammatory cytokines: Implications for treatment and diagnosis - Ahmed, E. M.; Ahmed, S. M.; Mohammed, Z. A.; Mohsein, O. A. (Regulatory Mechanisms in Biosystems, 2025)
Canker lesions are painful ulcerations affecting the oral mucosa, often linked to immune dysregulation. The aim of the study is investigate the relationship between canker lesions and inflammatory cytokines, exploring their potential role in disease progression. This study, conducted at Al-Habboubi Teaching Hospital and Nasiriyah General Hospital, enrolled 200 participants: 75 with diabetes, 75 without diabetes, and 50 healthy controls. Inclusion criteria included adults aged 40–60 years, while exclusion criteria excluded those with autoimmune diseases, immunosuppressive therapy, pregnancy, or recent infections. Blood samples were collected and processed for cytokine analysis (IL-6, TNF-α, IL-10, CRP, a diponectin) using ELISA and metabolic parameters (FBS, cholesterol, triglycerides) using spectrophotometry. Informed consent was obtained from all participants, and ethical approval was granted. The results showed no significant differences in age and gender between diabetic and non-diabetic individuals, while BMI was higher in diabetic patients. IL-6 and TNF-α levels were significantly elevated, whereas IL-10 was lower in diabetics compared to other groups. Diabetics also had higher amounts of CRP and fasting blood sugars, but lower levels of adiponectin. The amounts of total cholesterol, triglycerides, and LDL-C were higher in people with diabetes, while the levels of HDL-C were lower. The differences between diabetic and non-diabetic individuals were significant for all parameters, highlighting the inflammatory and metabolic effects associated with diabetes. Diabetic patients showed increased IL-6, TNF-α, CRP, glucose, and lipid levels, with d e creased IL-10 and adiponectin, indicating chronic inflammation and metabolic dysregulation. Elevated pro-inflammatory markers contribute to insulin resistance, while lower adiponectin affects lipid metabolism, increasing cardiovascular risk in diabetes.